2020
DOI: 10.1001/jamanetworkopen.2020.22906
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preexisting Interstitial Lung Abnormalities With Immune Checkpoint Inhibitor–Induced Interstitial Lung Disease Among Patients With Nonlung Cancers

Abstract: Key Points Question Are interstitial lung abnormalities, which are minor interstitial shadows on lung computed tomography, associated with immune checkpoint inhibitor induced–interstitial lung disease in patients with nonlung cancers? Findings In this cohort study of 199 patients with advanced nonlung cancers treated with anti–programmed cell death 1 antibody monotherapy, patients with preexisting interstitial lung abnormalities had significantly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…Conversely, interstitial pneumonia was correlated with symptomatic pneumonitis in this study. Similarly, some studies identified ILD as a risk factor for immune-mediated pneumonitis [ 15 18 ]. ILD is also a risk factor in radiation pneumonitis [ 36 , 37 ] and other anticancer drug-related pneumonitis cases [ 38 , 39 ], which should be noted in pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, interstitial pneumonia was correlated with symptomatic pneumonitis in this study. Similarly, some studies identified ILD as a risk factor for immune-mediated pneumonitis [ 15 18 ]. ILD is also a risk factor in radiation pneumonitis [ 36 , 37 ] and other anticancer drug-related pneumonitis cases [ 38 , 39 ], which should be noted in pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors with p -values < 0.10 in the univariate analysis were included in a multivariate model. ILD is the most common consensus clinical parameter related to the development of pneumonitis [ 15 18 ]. We selected ILD from previous studies and also selected the parameters from the results of univariate analysis and performed multivariate analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the effect of the existing ILD subtypes other than IPF was not investigated. As GGOs were reported to be an independent risk factor for ICI‐ILD in previous reports, 25,26 it is possible that there are populations with high AE risk among the ILDs classified as alternative diagnosis. To clarify the risk of AEs due to ICI in lung cancer complicated by ILDs, a large‐scale study including ILD patients with GGO‐dominant imaging patterns will be necessary.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the reasons for the association of ILA and lung cancer are not fully clear and future research must clarify whether it is a result of residual confounding or biological mechanisms [ 20 , 65 ]. On that note, ILA have been found to be a risk factor for postoperative complications after lung cancer surgery, such as ARDS, pneumonia and respiratory failure [ 66 ] as well as severe radiation pneumonitis after radiation for small cell lung cancer [ 67 , 68 ] and immune checkpoint inhibitor-induced interstitial lung disease among patients with lung cancer and other malignancies [ 69 , 70 ]. Among other outcomes associated with ILA in lung cancer screening studies are diagnoses of pneumonia, pleural empyema or lung abscesses, and respiratory failure [ 19 ].…”
Section: Clinical Outcomesmentioning
confidence: 99%